Design of a pitching delta wing in a free stream - He, Yueyu. (2011)
This final year project involves the design of a pitching delta wing subjected to a free stream in a water tunnel as well as investigating the hysteresis effect with vortex breakdown phenomenon associated with the pitching delta wing. A literature survey was carried out on the various experimental setups and delta wing configurations employed in past research journals. The experimental setup was designed taking into consideration past research experiments to ensure its feasibility, effectiveness, quality and safety to be carried out in the water tunnel situated in Nanyang Technological University: Aerospace Hangar. A motion control program was designed to control the parameters of the experiment in the oscillation of pitching delta wing while stepper motor was used to maneuver the pitching of delta wing. A fabricated aluminum delta wing was designed to promote vortex formation. Color dye injection technique was used to measure and visualize the vortex breakdown to obtain quantitative as well as qualitative results. The experiment was carried out in two parts. Firstly, flow visualization of delta wing in static position from 0° to 50° was carried out at a flow speed of 0.105 m/s at Reynolds number 15750. Secondly, flow visualization of an oscillating pitching delta wing with reduced frequencies of 0.23 and 0.34 from angle of attacks from 0° to 60° degree and reduced frequencies of 1.36, 1.70, 2.04 and 2.55 from angle of attack from 25° to 35°. Water flow velocity was at 0.105m/s at Reynolds number of 15750. The locations of vortex breakdown were recorded and analyzed. Phase lag was observed during oscillation of pitching delta wing which is a distinct trait in hysteresis effect. A higher degree of phase lag was observed as the reduced frequency increased. The experiment data matches past research journals’ data thus ensuring the validity of the experiment setup design.